High prevalence of blaOXA-23 in Acinetobacter spp. and detection of blaNDM-1 in A. soli in Cuba: report from National Surveillance Program (2010–2012). (September 2015) - Quiñones, D.; Carvajal, I.; Perez, Y.; Hart, M.; Perez, J.; Garcia, S.; Salazar, D.; Ghosh, S.; Kawaguchiya, M.; Aung, M.S.; Kobayashi, N.
Abstract: As a first national surveillance of Acinetobacter in Cuba, a total of 500 Acinetobacter spp. isolates recovered from 30 hospitals between 2010 and 2012 were studied. Acinetobacter baumannii–calcoaceticus complex accounted for 96.4% of all the Acinetobacter isolates, while other species were detected at low frequency ( A. junii 1.6%, A. lwoffii 1%, A. haemolyticus 0.8%, A. soli 0.2%). Resistance rates of isolates were 34–61% to third-generation cephalosporins, 49–50% to β-lactams/inhibitor combinations, 42–47% to aminoglycosides, 42–44% to carbapenems and 55% to ciprofloxacin. However, resistance rates to colistin, doxycycline, tetracycline and rifampin were less than 5%. Among carbapenem-resistant isolates, 75% harboured different bla OXA genes (OXA-23, 73%; OXA-24, 18%; OXA-58, 3%). The bla NDM-1 gene was identified in an A. soli strain, of which the species was confirmed by sequence analysis of 16S rRNA gene, rpoB, rpoB–rpoC and rpoL–rpoB intergenic spacer regions and gyrB. The sequences of bla NDM-1 and its surrounding genes were identical to those reported for plasmids of A. baumannii and A. lwoffi strains. This is the first report of bla NDM-1 in A. soli, together with a high prevalence of OXA-23 carbapenemase for carbapenem resistance in Acinetobacter spp. in Cuba.